Evaluation and Treatment of Hirsutism in Premenopausal Women: An Endocrine Society Clinical Practice Guideline - Martin, Kathryn A; Anderson, R Rox; Chang, R Jeffrey; Ehrmann, David A; Lobo, Rogerio A; Murad, M Hassan; Pugeat, Michel M; Rosenfield, Robert L (The journal of clinical endocrinology and metabolism, 2018)
Abstract Objective To update the “Evaluation and Treatment of Hirsutism in Premenopausal Women: An Endocrine Society Clinical Practice Guideline,” published by the Endocrine Society in 2008. Participants The participants include an Endocrine Society–appointed task force of seven medical experts and a methodologist. Evidence This evidence-based guideline was developed using the Grading of Recommendations, Assessment, Development, and Evaluation system to describe the strength of recommendations and the quality of evidence. The task force commissioned two systematic reviews and used the best available evidence from other published systematic reviews and individual studies. Consensus Process Group meetings, conference calls, and e-mail communications facilitated consensus development. Endocrine Society committees, members, and cosponsoring organizations reviewed and commented on preliminary drafts of the guidelines. Conclusion We suggest testing for elevated androgen levels in all women with an abnormal hirsutism score. We suggest against testing for elevated androgen levels in eumenorrheic women with unwanted local hair growth (i.e., in the absence of an abnormal hirsutism score). For most women with patient-important hirsutism despite cosmetic measures (shaving, plucking, waxing), we suggest starting with pharmacological therapy and adding direct hair removal methods (electrolysis, photoepilation) for those who desire additional cosmetic benefit. For women with mild hirsutism and no evidence of an endocrine disorder, we suggest either pharmacological therapy or direct hair removal methods. For pharmacological therapy, we suggest oral combined estrogen–progestin contraceptives for the majority of women, adding an antiandrogen after 6 months if the response is suboptimal. We recommend against antiandrogen monotherapy unless adequate contraception is used. We suggest against using insulin-lowering drugs. For most women who choose hair removal therapy, we suggest laser/photoepilation. An update of the “Evaluation and Treatment of Hirsutism in Premenopausal Women: An Endocrine Society Clinical Practice Guideline,” published by the Endocrine Society in 2008.